Hubungan AntaraPersepsi Terhadap Iklim Sekolah Dengan Motivasi Berprestasi Siswa - Eneng Nurlailiwangi; Yunita Sari; Riska Maryantika (SCHEMA (Journal of Psychological Research), 2011)
School is a place for learning and teaching process. Availability facilities and students interaction with all components of the school have an important role in the implementation of educational process. According to Baron and Kenny (1986), school climate affects students’ achievement motivation. Therefore, school must provide a school climate to get optimal learning outcomes. In reality, there is a lack of school which can provide that and can help their students in learning process, but their students have achievements. This phenomenon appears in Bandung X Elementary School. This research aimed to find out the strength of correlation between students’ perceptions on school climate and their achievement motivation in 5th grade who have achieved in SD X Bandung which has a poor school climate. This study will employ quantitative correlation design. The subject of this study is a population of 52 achiever students in 5th grade SD X. The instrument use to gather data for the first variable (students’ perceptions on school climate) will be questionnaire from Freidberg (1999) which was modified by the researcher and questionnaire of achievement motivation which was constructed according to the achievement motivation theory from Hermans (1967). The result of this study shows that there was correlation of rs= 0,697 that according to Guilford table, this score is entered into the moderate correlation. It means, there is a positive correlation between students’ perceptions on school climate and their achievement motivation. In addition, this study shows that there are several factors that influence the students’ perception on poor school climate, which is family background such as economic status, parents’ educational level, working parents, home environment experiences and patterns of parenting. Despite this school has a poor school climate, students who have achievement more focused on their achieved and achievement motivation rather than focusing on how the climate in their school.